Clinicopathological and Survival Analysis of Japanese Patients with Resected Non–Small-Cell Lung Cancer Harboring NKX2-1, SETDB1, MET, HER2, SOX2, FGFR1, or PIK3CA Gene Amplification. Issue 11 (November 2015) - Inoue, Yusuke; Matsuura, Shun; Kurabe, Nobuya; Kahyo, Tomoaki; Mori, Hiroki; Kawase, Akikazu; Karayama, Masato; Inui, Naoki; Funai, Kazuhito; Shinmura, Kazuya; Suda, Takafumi; Sugimura, Haruhiko
Abstract : Introduction: Gene amplification is an important genetic change in cancer cells. We investigated the prevalence, clinicopathological characteristics, and prognostic value of NKX2-1 (also known as TTF-1 ), SETDB1, MET, HER2, SOX2, FGFR1, and PIK3CA amplification in Japanese patients with non–small-cell lung cancer (NSCLC). Methods: The copy numbers of the seven above-mentioned genes were assessed using fluorescence in situ hybridization in a tissue microarray containing 282 surgically resected NSCLC specimens (164 adenocarcinoma [AC], 99 squamous cell carcinoma [SCC], and 19 others). Clinicopathological information were obtained from the medical records. Results: NKX2-1, SETDB1, MET, HER2, SOX2, FGFR1, and PIK3CA gene amplification were observed in 30 of 277 (10.8%), 16 of 280 (5.7%), 38 of 278 (13.7%), 8 of 270 (3.0%), 34 of 278 (12.2%), 18 of 282 (6.4%), and 53 of 278 (19.1%) cases, respectively. Coamplification was detected in 16 of 156 (10.3%) AC patients and 35 of 93 (37.6%) SCC patients ( p < 0.0001). NKX2-1 amplification was significantly related to an AC histology ( p = 0.004), whereas SOX2, FGFR1, and PIK3CA amplifications were related to a SCC histology ( p < 0.0001). Within the ACs, NKX2-1 and SETDB1 amplifications were markers of a shorter survival period. A multivariate Cox proportional hazards model revealed that NKX2-1 amplification was an independent predictor of poor survival (hazard ratio, 2.938; 95% confidence interval, 1.434–6.022; p = 0.003). Coamplification had impact on patient outcome in AC but not in entire NSCLC and SCC. Conclusions: The amplification status differed among the histological types of NSCLC. NKX2-1 amplification was an independent and the most practically important predictor of a poor prognosis among Japanese patients with AC.